Virginal. Goldemar Teilband I: Einleitung, 'Heidelberger Virginal'; Teilband II: 'Wiener Virginal'; Teilband III: 'Dresdner Virginal', 'Goldemar', Verzeichnisse - Lienert, Elisabeth; Pontini, Elisa; Schumacher, Katrin (Texte und Studien zur mittelhochdeutschen Heldenepik, 2017)
Virginal narrates a youthful tale by Dietrich von Bern: the liberation of Queen Virginal from a cruel heathen captor and other battles with heathens, giants, and dragons. The new edition offers three versions of the adventurous epic that differ in scope, wording, and the constitution of meaning, along with the thematically related Goldemar fragment.